Pengaruh Penanaman Modal Asing, Penanaman Modal Dalam Negeri Dan Belanja Modal Terhadap Pertumbuhan Ekonomi Provinsi Di Indonesia - Reza Lainatul Rizky; Grisvia Agustin; Imam Mukhlis (Universitas Negeri Malang, 2016)
This study is aimed to investigate the influence of foreign direct investments, domestic direct investments, and capital expenditures towards the Indonesia economic growth 2010-2013. Quantitative research design was employed in this study. The data used are secondary data with panel data. Panel data utilized cross section data comprising 33 provinces in Indonesia while the use of time series data in 2010-2013. The analysis method applied was panel regression analysis method with a Fixed Effect model. The result of this study demonstrated foreign direct investments, domestic direct investments, and capital expenditures have positive and significant influences towards provincial economic growth in Indonesia from the year 2010-2013 partially and simultaneously.Keywords: Foreign Direct Investment, Domestic Direct Investment, Capital Expenditure, Economic Growth